Determining Effect of Plyometric Exercises on Various Motoric Characteristics for Woman Volleyball Players - Mine Gül; Canan Eskiyecek; Hilal Şeşen; Gazanfer Gül (Türk Spor ve Egzersiz Dergisi, 2020)
Purpose of this study is to examine impacts on vertical jump, agility and 20 meter sprint run at the end of 8 weeks plyometric exercise program among 13-14 age group woman volleyball players. The study was carried out on 14 female athletes from the 13-14 age group of İzmit DSİ Sports Club whose sports age was 3.5 ± 0.70 years. Athletes were randomly divided into two groups as experimental (n=7) and control (n=7). Volleyball-specific technical-tactical trainings and plyometric training program were applied to the experimental group for 8 weeks, 3 days a week and 90 minutes in scope. The control group continued only 90 minutes of volleyball training. Prior to plyometric training, both groups were given agility, vertical jump and 20 meter speed tests as pre- and post-tests. First and last test values of the groups were determined and descriptive statistics were made by using SPSS 22.0 statistical package program. Wilcoxon test was used to compare the first and last measurements of the groups, and Mann-Whitney U test was used to compare the data of the control and experimental groups. According to the data obtained, when the experimental group first test and last test were compared, it was found that there was a statistically significant increase in vertical jump and illionis agility test results (p lt;0.05). There was no statistically significant difference between the 20 meter speed test values of the experimental group and all variables of the control group (p gt;0.05). There were statistically significant differences between the two groups in the comparison of the final measurement values of 20 meters speed, vertical jump and illinois agility test between the groups (p lt;0.05). As a result, it can be said that 8-week plyometric training has a positive effect on the speed, agility and vertical jump performance of volleyball players in the 13-14 age group.